Methods, Techinques and Researchers. Methodological Reflections on the Study of Disability - Pretto, Albertina (Espacio Abierto, 2018)
The article aims to offer some reflections and considerations arising from a case study regarding people with physical andsensory disabilities. Starting with a brief overview on theimportance of the qualitative method in the study of disability,and on the use of some qualitative research techniques appliedto this context, The article intends to highlight how, in somecases, qualitative interviews can provide better results thanother techniques. Nevertheless, some difficulties can emergealso using qualitative interviews, in particular with deafpeople. Moreover, since the research team included a disabled researcher, the article describes some problems that the latter (but not only) faced during the research.